2009
DOI: 10.1677/jme-08-0144
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid receptors, macrophages and cardiovascular disease

Abstract: The mineralocorticoid receptor (MR) and glucocorticoid receptor are ligand-activated transcription factors that have important physiological and pathophysiological actions in a broad range of cell types including monocytes and macrophages. While the glucocorticoids cortisol and corticosterone have well-described anti-inflammatory actions on both recruited and tissue resident macrophages, a role for the mineralocorticoid aldosterone in these cells is largely undefined. Emerging evidence, however, suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
50
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 122 publications
1
50
0
2
Order By: Relevance
“…Because this experiment included control rather than sham-operated animals, it is possible that cortisol released in response to the stress induced by surgery prevented a stronger osteoclast response in MKP1-deficient mice. 30 These results suggested, however, that MKP-1-deficient mice had osteoclasts that were hyperactive and hence were capable of resorbing equal quantities of bone compared with wild-type mice. We confirmed these results by inducing rapid formation and activation of osteoclasts in calvariae.…”
Section: Discussionmentioning
confidence: 97%
“…Because this experiment included control rather than sham-operated animals, it is possible that cortisol released in response to the stress induced by surgery prevented a stronger osteoclast response in MKP1-deficient mice. 30 These results suggested, however, that MKP-1-deficient mice had osteoclasts that were hyperactive and hence were capable of resorbing equal quantities of bone compared with wild-type mice. We confirmed these results by inducing rapid formation and activation of osteoclasts in calvariae.…”
Section: Discussionmentioning
confidence: 97%
“…As important tissue infl ammatory cells, macrophages undergo several stages of differentiation, including bone marrow hematopoietic stem cell, blood monocyte, and tissue macrophage ( 48 ). In diet-induced obesity, excess nutrition promotes more ATM recruitment and M1 polarization than in the normal diet state ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was not determined which cells in the kidney were involved in the effects of IMD-1041, for the same reason. Previous reports on tissue injury by aldosterone have clearly shown that inflammation plays important roles in the remodeling of the heart, vasculature, and kidney [26,27]. Furthermore, emerging evidence suggests that aldosterone receptors are present in various types of cells, including endothelial cells, macrophages, vascular smooth cells, cardiac cells, and renal tubular and glomerular cells, and that activation of the aldosterone receptor on these cells could induce inflammation in the organs [26,27].…”
Section: Discussionmentioning
confidence: 99%